The future of computing and wisdom: Insights from Human–Computer Interaction. (October 2019) - Pargman, Daniel Sapiens; Eriksson, Elina; Bates, Oliver; Kirman, Ben; Comber, Rob; Hedman, Anders; van den Broeck, Martijn
Highlights: This paper is a polyvocal discussion on wisdom that includes the fictional voices from researchers of 2068. We use "fictional abstracts" to elicit ideas and discuss present-day researchers' hopes and fears about future computing. While the design of technology can be informed by wisdom, we cannot imagine futures where technology itself is wise. Technological progress and wisdom change at different speeds which can create conflicts with our understanding of wisdom. What might sound like open-ended conversations can be seen as a precursor by designers and engineers to build "wise systems". Abstract: In this paper, we present a structured report on a dialogue on the Future of Computing and Wisdom. The dialogue consists of a recorded and transcribed discussion between researchers and practitioners in the field of Human–Computer Interaction that was held at workshop in conjunction with the 10th Nordic Conference on Human–Computer Interaction in September 2018. However, the dialogue also encompasses workshop participants' preparatory work with writing "fictional abstracts" – abstracts of yet-to-be-written research papers that will be published in 2068. The polyvocal dialogue that is reported upon thus includes not just the voices of researchers and practitioners who attended the workshop, but also includes the voices of the future researchers of 2068 who wrote the abstracts in question as well as the voices of the organisms, individuals, intelligent agents and communities who are the subjects, victims, beneficiaries and bystanders of wise (or unwise) future computing systems.